Role of Dermoscope as a Monitoring Tool in Assessing Treatment Response in Patients with Tinea Corporis: A Prospective Clinical Study - Aryal, Alisha; Shrestha, Merina; Bhattarai, Niraj (Journal of Nepalgunj Medical College, 2025)
Introduction: Tinea corporis is a common superficial dermatophytic infection affecting the glabrous skin. There is a prominent gap in research concerning the use of dermoscopy for monitoring treatment response in tinea corporis. Aims: To evaluate dermoscopic findings and assess the treatment response in patients with tinea corporis. Methods: A prospective clinical study was conducted at the Department of Dermatology, Nepalgunj Medical College and Teaching Hospital, involving 115 patients with tinea corporis over a 12-month period. Baseline dermoscopic examinations were performed for all participants. Patients were treated with oral itraconazole 100 mg twice daily and then re-evaluated with dermoscopy at 2 and 4 weeks. The frequency of various dermoscopic changes was analyzed using the chi-square test. Results: At baseline, the most common dermoscopic findings were erythema (98.3%), brown globules (83.5%), and perifollicular scales (80%). Micropustules were the first feature to resolve, disappearing within 2 weeks. Erythema, the predominant finding, showed significant reduction by 4 weeks (P = 0.005). Other features, including dotted vessels, perifollicular scales, brown globules, peripheral peeling scales, moth-eaten scales, translucent hairs, broken hairs, black dots, and telangiectasia, significantly decreased at 2 weeks, with further reduction observed by 4 weeks. Conclusion: Dermoscopy is a non-invasive, bedside tool that aids in the monitoring of treatment response in tinea corporis. It is particularly useful in identifying patients who may need extended systemic antifungal therapy to achieve a full resolution of the infection.